Pariwisata Bali Utara - Komang Bagas Parista Parmasta; Gede Eka Dharma Putra; I Putu Aditya Surya Pramana; Pande Putu Dwi Novigga Artha; I Wayan Runa (Undagi : Jurnal Ilmiah Jurusan Arsitektur Universitas Warmadewa, 2021)
Tourism in Bali has enormous potential to be introduced to the wider community, one of which is tourism in the North Bali area, the massive development and potential movement and documentation that makes tourism in North Bali famous. There is a lot of tourism in northern Bali, one of which is mostly natural, namely waterfalls, in every village in North Bali or what is commonly known as the Den Hill area, it almost has a waterfall. The flow of the waterfall is mostly centered in the Warnagiri area. With the development of this article about northern Bali, it intends to publish and also introduce a wider range of tours in this hillside area.